2012
DOI: 10.5430/jnep.v2n2p24
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the utility of the FamCHAT ethnocultural nursing assessment tool at a Canadian tertiary care hospital: A pilot study with recommendations for hospital management

Abstract: Objectives: The multicultural nature of Canadian society and the decline in health of immigrants after relocation to Canada prioritizes a commitment to ensure equity in health care access and outcomes. An important feature shaping health care access and outcomes is the reception of culturally safe and competent care. Partnering with senior management at a tertiary care hospital, this pilot study aimed to investigate whether an identified cultural assessment tool, the Family Cultural Heritage Assessment Tool (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This finding is supported by previous studies about immigrant health communication [ 15 , 18 , 67 , 68 ]. A language barrier not only hinders communication but also limits access to the information resources about availability of services [ 15 , 23 ]. Immigrant women who do not have information and knowledge about the availability of the services simply are not accessing these services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is supported by previous studies about immigrant health communication [ 15 , 18 , 67 , 68 ]. A language barrier not only hinders communication but also limits access to the information resources about availability of services [ 15 , 23 ]. Immigrant women who do not have information and knowledge about the availability of the services simply are not accessing these services.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the women continued to follow their healthcare beliefs and some experienced cultural shock when confronted with different healthcare practices such as the types of food served in maternity wards and less focused postnatal care. In a pluralistic multicultural society such as Canada, cultural competency of healthcare providers plays an important role in providing sufficient healthcare services with reduced risk of misunderstandings [ 23 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They had identified a clear need to enhance the quality of care for their increasingly diverse patient population. After the research team identified a potentially suitable tool (Higginbottom et al, 2011), we partnered with the senior management to conduct a pilot study aimed at investigating the suitability and acceptability of the identified cultural assessment tool -the Family Cultural Heritage Assessment Tool (FamCHAT) -in their setting (Higginbottom et al, 2012). The findings provided valuable information for the hospital management in their efforts to revise nursing assessment tools.…”
Section: Case 12 Participatory Research With Health Professionalsmentioning
confidence: 99%